(3bhi GdCOhjI GdeaQOI dLGdjfhSs - (3LGdjfhSs ((3ZQfGWI s)
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3Edi YfOeG GdJeSJ PcQ bhi GdCOhjI GdeaQOI ai gPG GdcJGH HjfJ efP Chd GdCeQ ai GdebGdJjf GdChdJjf efg GdePGgH GdbHjMI s
(3BNQgG (B:s
(3hbO GSJYedfG fMf CjVkG gPG GdbGfhf ai eOGhGI GdbQhM GdNGHKI ai GdbeQ deaQOI JQLeI Mfjf Hf ESMGb hHgPG Gced GdcJGH HMeO Gddg hYhfg s
(3GdSaQ GdKGfis
(3hjHOC Chdg HGdebGdI GdSGOSI ef cJGH LGdjfhS ai bhi GdCOhjI GdeaQOIs
(3hgj eGFI hKeGfjI hSJhf HGHkGs
(3hgj Yf fSNI cJHgG eMeO Hf CMeO Hf SdjeGf Hf SdeI GdCROi s
(3fSNI Yf fSNI cJHJ SfI (B502(3g` s
(3GfXQ agQS GdWH HQbe (B188 s
Keywords: (3GdWHs